Bank financing for small and medium enterprises: the case of two projects financed by Al Baraka Bank and the Bank for Agriculture and Rural Development - Belhadi , Sofiane (Journal of Research in Finance and Accounting, 2026)
Banks offer several financing formulas for small and medium enterprises, the most important of which are bank loans for conventional banks and participation for Islamic banksWhere traditional banks focus primarily in calculating their returns from the lending process on the interest rate, while Islamic banks focus in calculating their expected profits primarily on the participation rate in the project, We aim through this study to highlight the value of the trade-off between conventional and Islamic finance, and whether there are differences between them in cost. Among the most prominent results reached is that the comparison between the different financing formulas depends on three basic elements, the first is the cost of the financing formula, and the second is the expected advantages of the financing formula, As for the last element, it takes into account the general situation of the small and medium enterprise. That is, as the size of the institution increases, it is better for it to resort to traditional financing and vice versa, meaning the smaller the size of the institution, the better decision to resort to Islamic financing.